What Factors Affect College Tuition? A Guide to the Facts and Issues - Frances, Carol; American Association of State Colleges and Universities ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This report analyzes both the trends in college tuition paid by students, and the trends in higher education costs paid by institutions, and offers insights into the relationships between them. Data are presented to show that the annual rate of increase in college tuition has dropped significantly since the early 1980s. A four-factor model is presented to explain upward and downward pressures in total college tuition revenues; the model includes changes in enrollment, costs, share of total costs covered by student tuition, and resources invested. The report examines the legitimacy of comparing trends in college tuition with the Consumer Price Index and the Higher Education Price Index. The report then discusses: (1) the costs of particular goods and services purchased by colleges and universities; (2) trends in faculty and staff salaries and efforts to hold down compensation costs; (3) state higher education appropriations; (4) shortfalls in federal student aid funding; and (5) shortfalls in funding for research. The final two chapters fit tuition into the larger picture of college and university finance and analyze the outlook for college costs and college tuition in the 1990s. Forty-six charts illustrate the findings and are documented in the appendix by tables of data. (JDD)
Availability: AASCU Publications, One Dupont Circle, Suite 700, Washington, DC 20036.
Sponsoring Agency: Association of Urban Universities.
Sponsoring Agency: American Association of Community and Junior Colleges, Washington, DC.
Sponsoring Agency: American Association of Univ. Professors, Washington, DC.
Sponsoring Agency: American Federation of Teachers, Washington, DC.
May also be available online. Address as at 14/8/18
Keywords: Costs; Educational Finance; Educational Trends; Higher Education; Inflation (Economics); Models; Salaries; State Aid; Student Costs; Student Financial Aid; Trend Analysis; Tuition; Reports, Research; Numerical/Quantitative Data